The Role of Law in the New Institutional Economics - Rudolf Richter (Washington University Journal of Law & Policy, 2008)
To explain the role of law in the new institutional economics (NIE), we compare this approach with the economic analysis of law (EAL) of the 1970s when the NIE evolved. At that time the EAL was dominated by the “Chicago” or “market-based” approach that builds on the theory of perfect competition. Contracts are complete and Pareto efficient (allocative efficient). Ten years on, this approach was extended by informational economic models that are briefly touched upon here. After a few methodological considerations, the Article concentrates on the Williamsonian branch of NIE, i.e., the transaction cost approach (TCA). This theory argues that, in the real world of positive transaction costs, incomplete contracts can, at most, be efficient in a boundedly rational sense (“NIE-efficient”). The governance structure of contracts matters and becomes a bargaining point. Court ordering has to be complemented or substituted by private ordering. Attentive actors come to terms on a governance structure that protects them against ex post opportunistic maneuvers of their opponents. Generic governance structures are (according to Williamson) markets, hybrids, and hierarchies. Court ordering works best for market governance. In the case of hybrid modes (franchising, leasing, etc.), courts would mainly be supplanted by private ordering between the parties. As for hierarchies, courts would stay out of conflict resolution (fraud and conflict of interest excepted). While the objects of research in NIE and EAL remained different, the latter's methodology appears to move closer to that of NIE. Reprinted by permission of the publisher.
Keywords: Contracts; Law & amp; economics; Institutional economics; Contract theory; Competition (Economics); Law and economics (Jurisprudence); United States